Can the CERAD neuropsychological battery be used to assess cognitive impairment in Parkinson's disease? - Carlos Henrique Ferreira Camargo; Augusto Bronzini; Eduardo de Souza Tolentino; Camila Medyk; Gustavo Leopold Schultz-Pereira (Arquivos de Neuro-Psiquiatria)
ABSTRACT The Consortium to Establish a Registry for Alzheimer's Disease (CERAD) neuropsychological battery was created to assess cognitive impairment in Alzheimer's disease (AD) but it is widely-used for various dementias. The aim of this study was to analyze the efficacy of using the CERAD battery in the assessment of patients with Parkinson's disease. Forty-nine patients with Parkinson's disease were divided into two groups (one with dementia and one without) using the Movement Disorder Society criteria for Parkinson's disease dementia. Cognitive deficits were assessed with the Clinical Dementia Rating Scale as the gold standard, and the CERAD. The ROC curve for the CERAD battery had an area under the curve = 0.989 (95% CI = 0.967 – 1, p<0.0001). Among the CERAD subtests, verbal fluency had the worst accuracy, and word list learning had the best accuracy. Despite the limits of this study, the CERAD battery can be efficient for assessment of cognitive deficits in Parkinson's disease patients.